The Effect Of Hard Skills And Soft Skills On Treasurer Performance With Motivation As A Moderation Variable - Syamsuddin, Niswar; Kusumawati, Andi; Indrijawati, Aini (Jurnal Ekonomi, 2024)
Study This aim analyzes the influence of hard skills and soft skills on performance treasurer with motivation. Work as variable moderator at the Pompengan River Regional Center Jenberang. Study This used 90 samples consisting​ of treasurer at the Pompengan River Regional Center Jeneberang, selected using a random sampling technique. Data was collected through later questionnaire​ analysis using multiple linear regression and moderated regression analysis (MRA). Research results show that hard skills and soft skills have a positive influence on the performance of a treasurer. Apart from that, motivation Work moderates (strengthens) the influence of hard and soft skills on performance treasurer. Implications study: Improving the treasurer's hard and soft skills through training, development, and guard motivation is essential. Work treasurer through giving rewards, recognition, and opportunities to develop a career.